Knowledge of Malignant Bone Tumors in Children Among Parents in Majmaah Region - Abdulaziz F. Alkheraiji; Rakan B. Almjlad; Abdulaziz S. Alanzan; Rakan N. Almutairi; Mohammed A. Alqadhibi; Abdullah K. Alharbi; Abdullah F Abahussain; Abdullah M. Bin Aftan; Sultan H. Alruwaili; Abdulrahman F Alanazi; Yousef Tawfik Khoja (Journal of Pharmacy and Bioallied Sciences)
Objective: This study aimed to assess parents’ awareness and knowledge about childhood bone malignancies. Subjects and Methods: A cross-sectional study was conducted among parents in the Majmaah region of Saudi Arabia. A self-administered questionnaire was distributed among parents via an online survey. The questionnaire included sociodemographic data, a general awareness questionnaire regarding childhood bone malignancies, and a 13-item questionnaire to assess parents’ knowledge of childhood bone cancer. Results: Overall, 75% were considered to have poor knowledge about childhood bone cancer (mean score: 6.36 out of 13 points). Increased knowledge was more frequently observed among educated parents with higher monthly incomes, those who received education about childhood bone cancer from healthcare professionals, those who had experience with or exposure to a child with bone cancer, and those who were aware of vaccines that can help prevent certain types of childhood cancer. Conclusion: Parents’ knowledge about childhood bone malignancies was generally insufficient. However, better knowledge was more prevalent among educated parents with higher incomes and those who had more exposure to a child with cancer.